HEALTH CARE AND SPORT STUDENT ENGLISH LANGUAGE LEARNING STRATEGIES IN A LATVIAN HEI - Rudzinska, Ieva; Jakovleva, Monta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The aim of the research is to find out the characteristics of the English language learning strategy use in the students of two study Programs – Sport Science and Healthcare (Physiotherapy) in a Latvian higher education institution, using LLSU Inventory, developed in CARLA Center, University of Minnesota. The results show that both Program students are aware of the strategies and quite use them, mean = 2.63 for Listening Strategy and Vocabulary learning Strategy use, SD= .36 and .40 respectively. However, Physiotherapy student, e.g., use Listening Strategies more that the researched Sport Science students (Sig. (2-tailed) = .02, i.e., < .05)). Physiotherapy students more often “Plan out what to say or write in my own language and then translate it into the target language” (t=-2.12, Sig. (2-tailed) <.001).Although statistically significant small differences between both Program student languages learning strategy use were found, yet the strategy use of both Program students is generally the same. Program developers should consider the differences of student learning strategies; need to know which they students prefer, and which are still to develop.